Effect of growth regulators and Physiological Gradients on the High frequency plant regeneration from the long-term callus cultures of different germplasms of Rice (Oryza sativa L.) - Maruthi Rao, A; Sampath Kumar, I; Kavi Kishor, P B (Journal of Phytology, 2012)
Callus cultures of rice were initiated from mature embryos of different cultivars on LS medium containing 2 mg/L 2,4-D. Increasing concentrations of 2,4-D and 2,4-5T also increased the frequency of callus initiation in all the cultivars tested. Of different cultivars, Tellahamsa was found to be superior for callus initiation. Genotypic differences for plant regeneration were also observed. Cultivar Tellahamsa showed the highest (65-75%) frequency of plant differentiation followed by DGWG, Yerragaluvadlu, Surekha, Basmati-370, Bala, Chakko amubi, Jaya and IR-8. Callus cultures of rice cultivar Bala grown on a shoot-forming medium (LS + 1 mg/L IAA + 4 mg/L KN + 2% sucrose) were exposed to gibberellic acid and abscisic acid for varying lengths of time and at different periods during culture. Gibberellic acid totally suppressed the organogenesis in callus cultures of rice. The results suggest that if the tissue accumulated sufficient gibberellic acid prior to the initiation of meristemoids and shoot primordia, repression of shoot formation occurred. This repression was not reversed by increasing the levels of IAA and KN in the medium, but abscisic acid could partially overcome the gibberellic acid repression of shoot formation in rice callus. It has been observed in rice that shoots usually emerge from the basal portions of callus. This observation suggested that perhaps physiological gradients of materials were operative during the organ initiation process. To test this hypothesis, starch content and the enzyme activity of malate dehydrogenase in upper and lower portions of shoot-forming and non-shoot-forming callus were determined. Starch began to accumulate in both upper and lower portions of the shoot forming tissues within 4 days of culture. The rate of accumulation however, was faster and more in the lower portion of the callus leading to a peak of accumulation on day 8 in culture, i.e., prior to shoot formation. Non-shoot-forming callus cultures accumulated little starch during the same period of culture. Malate dehydrogenase (MDH) activity was examined in order to know the overall rate of respiration. In the upper segment of shoot-forming callus, the activity of MDH was very high by day 4 but declined continuously thereafter. The rate of activity of the enzyme was significantly higher beyond four days in culture in case of the lower portion of the shoot forming callus. Enzyme activity was lower in the non-shoot-forming portions (both upper and lower) of the callus. The higher rate of enzyme activity for the upper portion of the tissue could be attributed to increased oxygen availability. Thus, the evidence for the idea that concentrations of gradients or physiological gradients of substances into the callus tissue may be the operative factors promoting organ initiation in vitro is presented.